SAWT (Scientific Article Writing Training): Effectiveness in increasing Physics Teachers Competence as an Effort for Sustainable Professional Development of Teachers - Fadila, Sartina; Wiyono, Ketang; Ismet (Jurnal Pendidikan Indonesia, 2024)
Writing and publishing a scientific article is essential for teachers. These activities are part of the success indicators of teacher professional development and are included in the prerequisites for promotion. This research aims to determine the effect of the 4-phase scientific article writing training model on improving physics teachers' scientific article writing skills in South Sumatra. This type of research is a quasi-experiment using the pretest-posttest method. The population of this study was 35 physics teachers. The data analysis technique uses quantitative data collected from physics teachers' scientific article writing skill achievement scores. The research results show that applying the 4-phase scientific article training model can effectively improve teachers' skills in writing scientific articles to the point of successfully submitting them to accredited national journals Sinta 2 to Sinta 5. Implementing training activities using the suitable training model can have a positive impact on teachers so that it can comprehensively improve teacher skills and support the continuous professional development of physics teachers.